Houses on Fire: The Hauntologies of Sankomota - Swinney, Warrick (Kronos: Southern African Histories, 2024)
The following essay is part of a body of work titled Signal to Noise: sound and fury in (post)apartheid South Africa. These are a collection of creative nonfiction essays set against the backdrop of my involvement with a small, independent mobile recording studio based in Johannesburg between 1983 and 1997. The metaphor of a drowning signal, pushing through and making itself heard above the noise, resonates throughout the collection. The complexities of the political versus artistic nature of what we were involved with provide a setting for an anecdotal approach to what is part history, part biography, part memoir and part theoretical sonic exploration. The following essay falls into this approach and is constructed from memories enhanced by diaries, scrapbooks, shards of notes, lyrics, photos and conversations. These have been employed in reconstructing a narrative arc that covers the recording of the first album made by the band Sankomota, who were banned from entry into South Africa and were based in Maseru, mostly playing to audiences at one of the leading hotels. Sankomota, then called Uhuru, experienced extraordinary, almost metaphysical, peaks and troughs throughout their nearly thirty-year existence hence the hauntological device in the title.  The record was also the first made in our fledgling mobile studio using newly affordable equipment that kickstarted many such do-it-yourself projects worldwide. This was the first in a steady stream of technologies that would eventually break the hegemony of mainstream record companies. In apartheid South Africa, this was hugely significant, as being able to sideline the censorship of state-owned media enterprises meant immense freedom in the kind of projects one came to consider. Savage incidents of force and brutality were still common then, and our small venture has to be seen in the context of broader unrest and suffering. Frank Leepa was an uncompromising survivor. His words and melodies still move and inspire a younger generation.